Direct Measurement of Popular Price Expectations - Menil, George de; Bhalla, Surjit S. (American Economic Review, 2016)
Expectations are an important determinant of economic behavior. The analysis of economic expectations, however, has suffered from inadequate measurement. Throughout the literature, expectations have been treated as unobservable, and have therefore been measured only indirectly. The object of this paper is to develop and test a direct measure of the expectations of inflation, a particularly critical economic variable. A direct measure of inflationary expectations is here taken to be one constructed from a sample survey in which individuals are asked to state their expectations explicitly. The paper focuses on a popular forecast of the rate of change of consumer prices in the forthcoming year as calculated from responses to the Survey of Consumer Finances (SCF). This measure is presented in Section I. The SCF and others like it have existed for some time, but, a few recent studies notwithstanding, most economists continue to regard survey measures as inherently unreliable.' Their principal criticism is that the opinions an individual expresses